2004
DOI: 10.1099/ijs.0.02821-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the heterocystous cyanobacteria (subsections IV and V) based on nifD

Abstract: The heterocystous cyanobacteria are currently placed in subsections IV and V, which are distinguished by cellular division in one plane (false branching) and in more than one plane (true branching), respectively. Published phylogenies of 16S rRNA gene sequence data support the monophyly of the heterocystous cyanobacteria, with members of subsection V embedded within subsection IV. It has been postulated that members of subsection V arose from within subsection IV. Therefore, phylogenetic analysis of nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…This monophyletic cluster contains the orders Nostocales and Stigonematales (Sections IV and V) (Rippka et al, 1979), which were found to be intermixed (Turner et al, 1997(Turner et al, , 1999Gugger & Hoffmann, 2004;Henson et al, 2004). However, the genera Anabaena Born.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This monophyletic cluster contains the orders Nostocales and Stigonematales (Sections IV and V) (Rippka et al, 1979), which were found to be intermixed (Turner et al, 1997(Turner et al, , 1999Gugger & Hoffmann, 2004;Henson et al, 2004). However, the genera Anabaena Born.…”
Section: Introductionmentioning
confidence: 99%
“…Heterocytous cyanobacteria consistently form a monophyletic cluster among cyanobacteria on the basis of their 16S rRNA gene sequences (Wilmotte, 1994;Turner, 1997Turner, , 1999Wilmotte & Herdman, 2001;Lyra et al, 2001), RFLP and genomic fingerprinting (Lyra et al, 2001) and nifD sequences (Henson et al, 2004). This monophyletic cluster contains the orders Nostocales and Stigonematales (Sections IV and V) (Rippka et al, 1979), which were found to be intermixed (Turner et al, 1997(Turner et al, , 1999Gugger & Hoffmann, 2004;Henson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…According to the International Code of Botanical Nomenclature, the genus Nostoc belongs to the order Nostocales and, in Bergey's Manual of Systematic Bacteriology, it is affiliated to subsection IV of Cyanobacteria (Rippka et al, 2001). In recent phylogenetic studies, using several molecular marker genes (small subunit rRNA, rpoB, rbcLX and nifD or nifH), the closest relatives to the genus Nostoc were shown to be the genera Anabaena, Aphanizomenon and Trichormus, also members of the family Nostocaceae (Rajaniemi et al, 2005;Svenning et al, 2005;Henson et al, 2002Henson et al, , 2004Lohtander et al, 2003). All members of the genus Nostoc are characterized by a complex life cycle that includes differentiation into heterocytes (nitrogen-fixing cells), akinetes (resting spores) and hormogonia (motile filaments), serving for dispersion and as infective units in symbiosis (Lazaroff, 1966;Lazaroff & Vishniac, 1961;Mollenhauer, 1970;Rippka et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Cyanobacteria, an ancient gram-negative photosynthetic group of prokaryotes, are one of the most ubiquitously found groups of microbial species on earth (Henson et al 2004). Evolutionary assessments of cyanobacteria have indicated towards a sluggish pace of evolution as indicated by the similarity of the present forms to the fossilized forms (Henson et al 2002).…”
Section: Introductionmentioning
confidence: 99%